2018
DOI: 10.1371/journal.pone.0201967
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale forestry and carbon offset markets: An empirical study of Vermont Current Use forest landowner willingness to accept carbon credit programs

Abstract: This study investigates the preferences of small forest landowners regarding forest carbon credit programs while documenting characteristics of potentially successful frameworks. We designed hypothetical carbon credit programs with aggregated carbon offset projects and requirements of existing voluntary and compliance protocols in mind. We administered a mail survey to 992 forest landowners in Vermont’s Current Use Program utilizing best-worst choice, a novel preference elicitation technique, to elicit their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…In contrast, family forest landowners in the United States own on average 67.2 acres of forestland (Oswalt et al., 2019). Furthermore, feasibility studies have indicated that small‐scale forest owners do not meet the requirements for offset project permanence, accounting and monitoring, and are struggling with the rising costs of both the C inventory and accounting, as at least 1500–5000 acres are required to balance the transaction cost of participating in the offset market, depending on the stocking of the land (Kerchner & Keeton, 2015; Miller et al., 2014; White et al., 2018). Finally, project development and verification costs are high (more than $100,000 and $45,000, respectively), pushing market participation out of the reach of many family forest owners in the United States.…”
Section: Defining Ifmmentioning
confidence: 99%
“…In contrast, family forest landowners in the United States own on average 67.2 acres of forestland (Oswalt et al., 2019). Furthermore, feasibility studies have indicated that small‐scale forest owners do not meet the requirements for offset project permanence, accounting and monitoring, and are struggling with the rising costs of both the C inventory and accounting, as at least 1500–5000 acres are required to balance the transaction cost of participating in the offset market, depending on the stocking of the land (Kerchner & Keeton, 2015; Miller et al., 2014; White et al., 2018). Finally, project development and verification costs are high (more than $100,000 and $45,000, respectively), pushing market participation out of the reach of many family forest owners in the United States.…”
Section: Defining Ifmmentioning
confidence: 99%
“…Similarly, aggregated forest carbon offset projects incorporating a range of small forest landowners and coordinated by, for example, an NGO could address costly MRV and other transaction costs, potentially increasing the willingness of small-scale forest holders to participate (White et al 2018). Providing opportunities for funding to reduce transaction costs is important, especially in relation to MRV costs.…”
Section: Socio-economic Challengesmentioning
confidence: 99%
“…Options to participate in carbon payments have included the now defunct Chicago Climate Exchange (CCX, which ended in 2010 because of insufficient activity), various voluntary carbon market standards, the Regional Greenhouse Gas Initiative (RGGI) in nine northeastern states and the growing California Carbon Market. Several studies argue that there is potential for carbon payments to induce management changes, and more landowners would be willing to join if the price of carbon increases, although these results are based on hypothetical models or interviews with potential participants instead of actual participants' experiences [80][81][82]. With the historically and currently low price of carbon, other studies have found that very few landowners are willing to actually join [80,81,83].…”
Section: Us Private Forestlands and Cdrmentioning
confidence: 99%